Masa Depan Arbitrase sebagai Mekanisme Penyelesaian Perselisihan Hubungan Industrial di Indonesia - Mila Karmila Adi (Fakultas Hukum Universitas Islam Indonesia, 2010)
The unresolved clash between the employees and employers may result a fire or resignation. Generally, it makes the unexpected condition worse for both. In the case of a fire, the employees will face a bad future without job. The research is focused on the arbitrary possibility as a solution for their need to solve the clash between employees and employers. It is done through normative and comparative approach, and secondary data analysis. The result shows that an arbitrary has three characteristics; they are simple, fast and cheap, which is suitable to maintain a good working relationship in Indonesia. Yet, it has some weaknesses that mainly relate to expense and fee for the arbitrary team paid by those parties. Thus, this arbitrary mechanism is unlikely to be used in majority.Key words : Arbitrage, employment relationship, and dispute resolution